A Bibliometric Analysis of Implementing Project Management on Construction Workers in Mining Building Projects - Tuswoyo Tuswoyo; Ahmad Hidayat; Ade Arqam Hidayat (Dinasti Publisher, 2025)
The application of project management is very often used in construction work for mining industry buildings and city facilities, with various methods in line with the demands of the times and technology, so it is necessary to study the application of construction project management that supports the mining process. The literature review aims to systematically obtain information on the development of scientific research in construction project management as a measure of understanding the current and future progress of the production of scientific studies using a quantitative review technique called bibliometric analysis, data taken from the Scopus and Google Scholar databases using publish or software. Perish (PoP) and Mendeley were then analyzed using VOSviewer software. Of the 1009 journal articles, only 867 were selected, based on the most relevant terms and words to be analyzed. The results of the analysis show that in the field of project management, industrial construction buildings and safety are the most dominant topics with the largest cluster, namely project management. The total articles obtained from 2015 to 2023, show that the construction sector cluster topic relating to safety and labor is the latest research. during the pandemic. Overall, this research can be used by researchers as a basis for future research on topics that require further study, namely safety culture and local culture to create good workforce performance as measured by the level of job satisfaction and employee satisfaction as project owners using the latest technology.